1982
DOI: 10.1111/j.1365-2621.1982.tb12730.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitrite and Sorbate on Total Number of Aerobic Microorganisms in Chicken White and Dark Meat Patties

Abstract: The effects of nitrite, sorbate and combinations of these two ingredients plus salt on the number of aerobic microorganisms in chicken white and dark meat patties were examined. All patties were stored at 4-5°C for 12 days. Nitrite concentrations of 400 and 2500 ppm were effective in preventing bacterial growth in chicken white meat patties while 2500 ppm was required to prevent growth in dark meat. A reduction in bacterial growth (4-10 days) was demonstrated with 100 and 150 ppm nitrite in chicken white meat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0
2

Year Published

1984
1984
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 15 publications
1
0
0
2
Order By: Relevance
“…Bacterial counts also significantly increased with storage time (Table 11). These data agree with those of Kraft et al (1979) and Bushway et al (1982) who reported that increased storage time and decreased levels of sodium nitrite resulted in increased numbers of microorganisms in meat formulations. ' ' ' ' Means with same superscript in same column did not differ statistically (P<.05).…”
Section: Resultssupporting
confidence: 93%
“…Bacterial counts also significantly increased with storage time (Table 11). These data agree with those of Kraft et al (1979) and Bushway et al (1982) who reported that increased storage time and decreased levels of sodium nitrite resulted in increased numbers of microorganisms in meat formulations. ' ' ' ' Means with same superscript in same column did not differ statistically (P<.05).…”
Section: Resultssupporting
confidence: 93%
“…O nitrito é uma molécula reativa a qual pode modificar diversos componentes celulares, entretanto as modificações que realmente contribuem para a ação conservante do nitrito não são tão simples de serem compreendidas (Buchman & Hansen, 1987 A maioria dos alimentos processados é formulada com um certo nível de nitrito, porém devido à formação de nitrosaminas, novos estudos estão sendo direcionados para encontrar uma alternativa para a eliminação ou redução nos níveis de nitrito adicionado (Bushway et al, 1982;Lin et al, 1980;Vareltziz et al, 1984).…”
Section: Efeito Bacteriostático Em Microrganismos Aeróbiosunclassified
“…A ausência da atividade do nitrito, em relação à diminuição não significativa da carga bacteriológica nas CMSs analisadas, pode ser discutida de acordo com Bushway et al (1982). Tais pesquisadores verificando o efeito do nitrito no número de microrganismos aeróbios em hambúrgueres de carne clara e escura de frango obtiveram resultados controversos.…”
Section: Contagem Dos Microrganismos Nas Cmss Tratadas E Congeladas Nunclassified